2022
DOI: 10.1161/jaha.121.022214
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Changes in Left and Right Ventricular Cardiac Magnetic Resonance Feature Tracking Strain Following Ferric Carboxymaltose in Patients With Heart Failure: A Substudy of the Myocardial‐IRON Trial

Abstract: Background The mechanisms explaining the clinical benefits of ferric carboximaltose (FCM) in patients with heart failure, reduced or intermediate left ventricular ejection fraction, and iron deficiency remain not fully clarified. The Myocardial‐IRON trial showed short‐term cardiac magnetic resonance (CMR) changes suggesting myocardial iron repletion following administration of FCM but failed to find a significant increase in left ventricular ejection fraction in the whole sample. Conversely, the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…An important finding of this study was the correlation between salt intake and myocardial strain rates. The myocardial strain rate has been demonstrated to be a direct and sensitive evaluation index for myocardial viability and early changes in cardiac function ( 10 13 ). In this study, we found significant differences in global SRe, SRa, and SRs between individuals with higher salt intake and those with lower salt intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important finding of this study was the correlation between salt intake and myocardial strain rates. The myocardial strain rate has been demonstrated to be a direct and sensitive evaluation index for myocardial viability and early changes in cardiac function ( 10 13 ). In this study, we found significant differences in global SRe, SRa, and SRs between individuals with higher salt intake and those with lower salt intake.…”
Section: Discussionmentioning
confidence: 99%
“…The strain rate (SR) is a sensitive and direct index of myocardial viability and changes in cardiac function ( 10 13 ). SR quantifies the velocity of myocardial contraction and correlates with cardiomyocyte hypertrophy and fibrosis ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…17 In addition, all global 2D strain parameters of the right ventricle, assessed with CMR, were improved 30 days after FCM therapy. 11 The analysis by Martens et al provides evidence for more sustained favourable changes in RV function, 3 months after FCM therapy, with preliminary findings of reverse remodelling as evident from reduced RV end-systolic and end-diastolic areas. The remodelling findings, however, will need additional confirmation.…”
Section: This Article Refers To 'The Effect Of Intravenous Ferric Car...mentioning
confidence: 98%
“…In a recently reported sub-study of the Myocardial-IRON trial, which evaluated whether ferric carboxymaltose (FCM) repletes myocardial iron better than placebo in patients with HF and LVEF <50%, analysis of ventricular mechanics with cardiac magnetic resonance (CMR) demonstrated improvement of global three-dimensional left ventricular (LV) strain parameters 30 days after FCM administration. 11 Of note, the main Myocardial-IRON trial reported CMR findings consistent with myocardial iron repletion with FCM, but the improvement in LVEF was not significantly better in the FCM arm versus placebo, suggesting that LVEF alone may not be sensitive enough to detect beneficial metabolic effects of iron supplementation on myocardial function. 12 There are even more limited data on the effect of iron supplementation therapy on right ventricular (RV) function and 13 published in this issue of the Journal is an important addition to the literature.…”
Section: This Article Refers To 'The Effect Of Intravenous Ferric Car...mentioning
confidence: 99%
See 1 more Smart Citation